Using a Model MAP to prepare hydro-meteorological models for generic use. (November 2015) - Harpham, Quillon
Abstract: Structured environments for executing environmental numerical models are becoming increasingly common, typically including functions for discovering models, running and integrating them. As these environments proliferate and mature, a set of topics is emerging as common ground between them. This paper abstracts common characteristics from leading integrated modelling technologies and derives a generic framework, characterised as a Model MAP – Metadata (including documentation and licence), Adaptors (to common standards) and Portability (of model components). The idea is to form a gateway concept consisting of a checklist of elements which must be in place before a numerical model is offered for interoperability in a structured environment and at a level of abstraction suitable to support environmental model interoperability in general. Following comparison to the Component-Based Water Resource Model Ontology, the Model MAP is applied to DRIHM, an hydro-meteorological research infrastructure, as the initial use case and more generic aspects are also discussed. Highlights: A gateway set of requirements for legacy environmental model interoperability. A route towards legacy environmental model standardisation. Comparison to the Component-Based Water Resource Model Ontology. Application of the Model MAP for a hydro-meteorological model eInfrastructure. Applying the Model MAP to WRF-ARW and an OpenMI composition.